The Utilization of School Library As Learning Resources at Anak Saleh Primary School Malang City - Amaliya, Fierda Nursitasari (Universitas Negeri Makassar, 2025)
Abstract: This study aims to describe the use of libraries as a learningresource, roles and functions of library use, and supporting and inhibitingfactors in using libraries at SD Anak Saleh Malang City. This researchuses descriptive qualitative. The subjects of this study were librarian,class I-VI teachers, and grade I-VI students. The results of the analysisconcluded that the use of the library as a learning resource was runningwell. Based on the results of this study, the school is advised to addlibrary staff and for librarians to add to the collection of books accordingto the needs and interests of students.Keywords: Utilization, SD Libraries, Learning Resources